2019
DOI: 10.1044/2019_jslhr-l-18-0367
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Language and Planning in Children With Language Impairment

Abstract: Purpose This study examined the relationship between language and planning, a higher order executive function skill, in children with specific language impairment (SLI) and typically developing (TD) children. We hypothesized differences between groups in planning performance and in the role of verbal mediation during planning. Method Thirty-one children with SLI and 50 TD age-matched peers (8–12 years) participated in the study. We assessed language abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…Additionally, the SOB‐CS model does not make specific predictions regarding the role of rehearsal in working memory (Oberauer et al., 2012) whereas other models of working memory (e.g., decay‐based models) do make such predictions. It is possible that rehearsal strategies, such as verbal mediation and attentional refreshing, were deployed differently in our DLD and TD groups, and it is possible that the relationship between rehearsal and working memory performance differed between the DLD and TD groups (e.g., Larson et al., 2019). Future work should explore these possibilities, as well as how other models of working memory may account for phenomena observed in the current study (Oberauer et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the SOB‐CS model does not make specific predictions regarding the role of rehearsal in working memory (Oberauer et al., 2012) whereas other models of working memory (e.g., decay‐based models) do make such predictions. It is possible that rehearsal strategies, such as verbal mediation and attentional refreshing, were deployed differently in our DLD and TD groups, and it is possible that the relationship between rehearsal and working memory performance differed between the DLD and TD groups (e.g., Larson et al., 2019). Future work should explore these possibilities, as well as how other models of working memory may account for phenomena observed in the current study (Oberauer et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Though we used a measure of language that captures the key area of weakness in language impairment, grammar skills, in our analyses, we were not able to examine within subgroup patterns. Future research would benefit from analyzing this subgroup to better understand structural language impairment in ASD, the possibility of overlapping patterns of findings with peers who have developmental language disorder (e.g., Larson et al, 2019), and the possibility of more similar patterns between NT peers and autistic individuals with relatively strong language skills than autistic individuals who experience structural language challenges. Also, investigating the potential role of spatial cognition and performance on mental rotation tasks for success at word learning may be informative.…”
Section: Limitationsmentioning
confidence: 99%
“…In these autistic individuals with relatively poor structural language skills, there may be an even greater dissociation between language and cognitive systems or greater discrepancy between these systems. Larson et al (2021) showed that individuals with ASD and co‐occurring structural language impairment used verbal mediation to a lesser degree than autistic peers without structural language impairment, and both of these groups used verbal mediation to a lesser degree than NT peers on a visuospatial planning task (see also Larson et al, 2019, for similar patterns in a developmental language disorder group and Johnston & Ellis Weismer, 1983, for evidence of poorer mental rotation in individuals with language disorder). Ellis Weismer et al (2018) also demonstrated links between language and performance on several visuospatial executive function tasks that differed in ASD relative to NT peers and in autistic individuals with versus without co‐occurring structural language impairment.…”
Section: Introductionmentioning
confidence: 99%
“…In children around the age of 6 years, self-directed speech typically starts to internalize (it “goes underground;” Vygotsky, 1934/1986 , p. 34) until it finally becomes silent (i.e., inner speech; Vygotsky, 1934/1986 ; Bivens and Berk, 1990 ; Damianova et al, 2012 ). In children with language problems, this internalization process appears to be delayed (i.e., inner speech and private speech emerge at a later age; Lidstone et al, 2012 ; Aziz et al, 2017 ), and they draw upon it to a lesser degree in planning (Kuvalja et al, 2014 ; Larson et al, 2019 ).…”
Section: The Interplay Between Self-directed Speech Ef and Tom In Imentioning
confidence: 99%